Comparison of VO2 Max Prediction Value, Physiological Response, and Borg Scale between 12-Minute and 3200-Meter Run Fitness Tests among Indonesian Army Soldiers - Maulidi Abdillah; Tertianto Prabowo; Marietta Shanti Prananta (Faculty of Medicine Universitas Padjadjaran, 2016)
Objective: To compare the VO2 max and physiological responses between 12-minute and 3200-meter run fitness tests.Methods: The subjects were 40 soldiers aged 18–21 years old of the Infantry Battalion 303/SSM of Cikajang, Garut, West Java, Indonesia. The 12-minute and 3200-meter run fitness tests were conducted with one week resting period. The measurement of the VO2 max prediction was based on each of the formulations and the measurement of physiological response included blood pressure, heart rate, respiratory rate, Borg scale and oxygen saturation before and after the tests. This study used a cross-sectional method while the data were analyzed statistically using t-test (p=0.05). Results: The results showed that the VO2 max prediction in 12-minute run fitness test was 52.046±2.980 mL/KgBB/min and the 3200-meter run test was 55.323±3.238 mL/KgBB/min. The value was statistically significant (p=0.008). There was no significant difference in the physiological response in both tests, except the SpO2 parameter after the tests (p=0.021). Conclusions: There is a significant difference in VO2 max prediction between 12 minutes and 3200 meter run test. No significant difference was found in the physiological response in both tests, except the SpO2 parameter. Keywords: 12-minute run fitness test, 3200-meter run fitness test, physiological response, soldiers, VO2 max DOI: 10.15850/ijihs.v4n2.836